Study on Employee Mental Health and Stress Management Due to Artificial Intelligence and Robotics - Jyotindra Jani (International Journal of Robotics and Automation in Mechanics, 2024)
The introduction of Artificial Intelligence (AI) and robotics in the workplace raises important questions about the impact of these technologies on employee mental health and stress management. This study aims to explore the potential effects of these technologies on employee mental health, wellbeing and stress levels. The study will focus on the role of AI and robotics in the workplace, the potential impacts of these technologies on employee mental health and stress management strategies, and the implications for employers in terms of providing support to workers affected by the introduction of AI and robotics. The findings of the study will provide insight into the potential effects of AI and robotics on employee mental health and stress management, and inform employers on strategies to support workers affected by the introduction of these technologies.
Keywords: AI robotics; Automation; Employee mental health; stress management